2019
DOI: 10.1136/bmjopen-2018-028252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supervised exercise training during pregnancy on psychological well-being among overweight and obese women: secondary analyses of the ETIP-trial, a randomised controlled trial

Abstract: ObjectivesWomen with high body mass index (BMI) have increased risk for symptoms of anxiety and depression during pregnancy and postpartum. In this prespecified secondary analysis from the exercise training in pregnancy trial, our aim was to examine effects of supervised exercise during pregnancy on psychological well-being in late pregnancy and postpartum among women with a prepregnancy BMI ≥28 kg/m2.DesignSingle-centre, parallel group, randomised controlled trial.SettingUniversity Hospital, Norway.Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Currently, many studies have suggested that physical exercise, as an alternative and complimentary therapy, has a positive effect on psychological health (Tsang et al, 2008 ; Chen et al, 2012 ; Li et al, 2015 ; Epps et al, 2019 ; Garnaes et al, 2019 ). Qigong exercise is an easily adaptable form of mind-body integrative exercise whose basic components include thoughts concentration, relaxation, meditation, breathing regulation, body posture, and gentle movement (Tsang et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many studies have suggested that physical exercise, as an alternative and complimentary therapy, has a positive effect on psychological health (Tsang et al, 2008 ; Chen et al, 2012 ; Li et al, 2015 ; Epps et al, 2019 ; Garnaes et al, 2019 ). Qigong exercise is an easily adaptable form of mind-body integrative exercise whose basic components include thoughts concentration, relaxation, meditation, breathing regulation, body posture, and gentle movement (Tsang et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, a quick rise in blood pressure and intra-abdominal pressure is triggered by heavy strength training during pregnancy, which may momentarily reduce blood flow to the fetus. However, resistance exercise with a modest to moderate load had no negative consequences during pregnancy [ 40 ]. Resistance exercise with elastic belts for 2–3 repetitive sets of movements, or through self-muscle exercises that involve upper and lower limbs for 2–3 sets of 12–24 repetitions, would fit well in pregnancy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, full-text articles for 62 references were assessed for eligibility to be included in the study. The final articles included for the review are 12 studies [10][11][12][13][14][15][16][17][18][19][20][21]. Meta-analysis study includes 11 RCTs out of 12, and one study was excluded due to unfitting data for measurement of outcomes [10].…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…All the studies included for analysis were published between the years 2011 and 2019 in English as shown in Table 1. Most of the randomized controlled trial is conducted in a developed country; three in Norway [10][11][12], three in Spain [13,17,19], and each one study in Ireland [15], New Zealand [18], United States [20], and the Netherlands [16], while the remaining two studies are conducted in developing countries; each one study in China [14] and Brazil [21]. In terms of the author, Garnaes et al was the author of three studies, and each of the studies was analyzed as an individual study because they measured several different outcomes and the studies are published in a different time [10][11][12].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation